Eradicating Mosquito Nests Through Draining, Covering and Burying Efforts with the Presence of Mosquito Larvae - Musiana, Musiana; Adam, Muhammad Andi (International Journal of Health Sciences, 2023)
In Southeast Sulawesi, measures have been taken to prevent dengue hemorrhagic fever with vector control efforts using the 3M Plus method, namely draining, covering and burying items that are no longer used so that they do not become breeding places for mosquitoes. The aim of the research is to take measures to prevent dengue hemorrhagic fever by controlling vectors using the 3M Plus method, namely draining, covering and burying items that are no longer used so that they do not become breeding places for mosquitoes. Meanwhile, the plus is avoiding mosquito bites by using anti-mosquito lotion, wearing a mosquito net when sleeping, abatization, fishization and fogging. With these efforts, it is hoped that the death rate due to dengue hemorrhagic fever can be reduced. This research is a survey research with a cross sectional study approach. The variables in this research are the independent variable (draining, covering, burying used goods and abatement) and the dependent variable (presence of mosquito larvae). The result is that the Chi Square statistical test on the variable draining water reservoirs shows a p value = 0.000<0.05, which means that H0 is rejected and Ha is accepted, so the statistical test shows that there is a relationship between draining water reservoirs and the presence of mosquito larvae. The Chi Square statistical test on the variable closing water reservoirs shows a p value = 0.003<0.05, which means that H0 is rejected and Ha is accepted, so the statistical test shows that there is a relationship between closing water reservoirs and the presence of mosquito larvae. The Chi Square statistical test on the variable burying used goods shows a p value = 0.000 < 0.05, which means that H0 is rejected and Ha is accepted, so the statistical test shows that there is a relationship between burying used goods and the presence of mosquito larvae.